1866 Tex. Gen. Laws 210, An Act To Prohibit The Discharging Of Fire Arms In Certain Places Herein Named, chap. 170, § 1 - (:unkn) unknown (My University, 1866)
It shall not be lawful for any person to discharge any gun, pistol, or fire arms of any description whatever, on, or across any public square, street, or alley, in any city or town in this state; Provided this act shall not be so construed as to apply to the "outer town," or suburbs, of any city or town.
Keywords: DISCHARGE